A prospective study to evaluate the acceptance, efficacy, side effects and expulsion rates of post-placental intrauterine device - Sankhe, Richa S.; Kamble, Meenal T. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: This study was conducted to know the factors associated with acceptability of immediate post placental IUCD insertion in women and to know the level of safety, efficacy and expulsion of post placental insertion of IUCD. Methods: This study was conducted in Obstetrics and Gynecology Department of Kasturba General Hospital, Mumbai over a period of 1 year. Women admitted and delivered at KGH were informed and counselled regarding intrauterine devices regarding its insertion, efficacy and side effects. Cu T 380A was inserted within 15 minutes of delivery of placenta and membranes in women who gave consent and had no contraindications for IUD insertion. All these women were followed for 6 months in the post insertion period. Results: Total number of women counselled was 400 over the period of six months from August 2015 to January 2016. Out of these only 250 women gave consent for PPIUCD insertion. 50 were lost to follow up. 200 women were followed, out of which 15 women had expulsion, 15 women had excessive bleeding, 20 women complained of pelvic pain, bleeding and abdominal pain together was found in 25 women. 160 out of 200 continued with the method while the rest discontinued. Conclusions: Based on present study it may be concluded that post placental intrauterine device is an effective method of contraception. Proper counselling and insertion techniques would further improve the acceptability and reduce the expulsion rates.